2004
DOI: 10.1111/j.1526-4637.2004.04019.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Chronic Neuropathic Pain

Abstract: Neuropathic pain arises from a lesion or dysfunction within the nervous system; the specific mechanisms that elicit neuropathic pain symptoms are the subject of ongoing research. It is generally acknowledged that neuropathic pain is extremely difficult to treat, and a major factor impacting outcomes is the presence of comorbidities such as poor sleep, depressed mood, and anxiety. Patients who suffer from chronic pain experience difficulties in initiating and maintaining sleep. Sleep deprivation has been associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
163
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(173 citation statements)
references
References 94 publications
(109 reference statements)
4
163
0
2
Order By: Relevance
“…This category consists of words related to the individual's emotional state, and can translate the perception of tiredness, the feeling of fear and punishment and autonomic reactions. These data confirm the idea that individuals with neuropathic pain present emotional factors related to the perception of this symptom 41 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This category consists of words related to the individual's emotional state, and can translate the perception of tiredness, the feeling of fear and punishment and autonomic reactions. These data confirm the idea that individuals with neuropathic pain present emotional factors related to the perception of this symptom 41 .…”
Section: Discussionsupporting
confidence: 79%
“…When the reliability of the Sensory Pain Classification Index was assessed, it showed to be almost perfect, demonstrating the importance of this category to qualify pain in this specific elderly group. It is noteworthy that the sensory characteristics of pain are the main criteria to define the presence of neuropathic pain 40,41 . There are several mechanisms to develop neuropathic pain, such as direct stimulation of the sensitive neurons by compression or chemical irritation, by nervous injury or deafferenting and maintenance of pain by constant sympathetic stimulation [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…[61] Although chronic pain can contribute to the development of depression, anxiety, stress, and sleep disorders, these factors exhibit a bi-directional relationship with pain and their presence can lower pain thresholds, influence perception, and increase the risk of developing chronic pain. [62][63][64][65][66][67][68] Even basic steps to assess and address an individual's psychological and social factors can significantly increase the likelihood of treatment success. This requires an individualized treatment approach that shifts from predominantly biomedical strategies (i.e.…”
Section: Understanding Chronic Painmentioning
confidence: 99%
“…Pain and reward are considered opponent processes, but are processed within overlapping or interacting brain structures (e.g., anterior cingulate cortex, dorsal and ventral striatum, and amygdala). It has been demonstrated that rewarding stimuli such as food and pleasurable music decrease pain sensitivity [12], whereas pain can impair reward processing, which can lead to an anhedonic state [13,14]. The negative affect, or how much the pain is 'bothersome,' significantly impacts the quality of life of the sufferer, and leads to the common comorbidities of psychiatric disorders such as depression.…”
Section: Introductionmentioning
confidence: 99%
“…The negative affect, or how much the pain is 'bothersome,' significantly impacts the quality of life of the sufferer, and leads to the common comorbidities of psychiatric disorders such as depression. Comorbidity between chronic pain and Axis I disorders of the DSM-V (including depression, anxiety disorders, bipolar disorder, ADHD, autism spectrum disorders, and schizophrenia) has been well documented, where depression is the most common comorbidity, with some studies finding a prevalence rate approaching 100 % among clinical chronic pain samples [14]. In fact, chronic pain is second only to bipolar disorder as the major cause of suicide among all medical illnesses, and the high comorbidity of migraine with depression further highlights the importance of negative affect [15][16][17].…”
Section: Introductionmentioning
confidence: 99%